Transdisciplinary Research and Aboriginal Knowledge - Christie, Michael (The Australian Journal of Indigenous Education, 2006)
Abstract Indigenous academic researchers are involved in Indigenist, interdisciplinary and transdisciplinary research, all of which present problems and opportunities for Indigenous knowledge traditions. Transdisciplinaryresearch is different from interdisciplinaryresearch because it moves beyond the disciplinarity of the university and takes into account knowledge practices which the university will never fully understand. Indigenous knowledge traditions resist definition from a Western academic perspective - there are Indigenous knowledge practices which will never engage with the academy, just as there are some branches of the academy which will never acknowledge Indigenous knowledge practices. In this paper I present the story of my own non-Indigenous perspective on Indigenous research and what happens to it in a university. I am not concerned here with the knowledge production work Aboriginal people do in their own ways and contexts for their own purposes, but rather turn my attention to some of the issues which emerge when transdisciplinary research practice involves Australian Indigenous communities.